The Impact of Public Awareness, Infrastructure Availability, and Government Regulations on the Effectiveness of Waste Management in Cimahi City - Abrori, Abrori; Sunarti, Sunarti; Puspita, Marina; Darmawan, Indra (Westscience Press, 2025)
This study examines the impact of public awareness, infrastructure availability, and government regulations on the effectiveness of waste management in Cimahi City. A quantitative approach was employed, utilizing a sample of 250 community members and a Likert scale (1-5) for data collection. Structural Equation Modeling - Partial Least Squares (SEM-PLS 3) was used for data analysis. The findings indicate that all three factors significantly influence waste management effectiveness, with public awareness, infrastructure availability, and government regulations contributing positively. The model explains 72% of the variance in waste management effectiveness, demonstrating a strong explanatory power. These results emphasize the need for an integrated approach that combines public education, infrastructure investment, and regulatory measures to enhance waste management practices. The study provides valuable insights for policymakers and practitioners aiming to improve waste management systems in urban settings.